An Analysis of Teacher’s Strategies in Teaching Reading Skill at Junior High School - Kosassy, Siti Annisa; Suparmi, S; Sari, Rosi Kumala (SAFE-Network, 2024)
The purpose of this study was to describe the teacher's strategy in teaching English reading skills at a Junior High School, namely State Junior High School (SMP N) 5 Padang. Reading skills are needed by students in conveying their goals in order to make them fluent in reading English. In achieving this lesson goal, teachers need good and interesting strategies to make it easier for students to understand the material. This study was conducted using descriptive qualitative research. Descriptive qualitative research is to describe the teacher's experience in teaching English reading skills at SMP N 5 Padang. For participants involved 2 English teachers at SMP N 5 Padang. This study used two instruments, namely observation and interviews. The results of the study showed that teachers used 6 strategies in teaching English reading skills, namely predicting, making connections, summarizing, asking, visualizing. The results obtained in this study are making connections and summarizing techniques are the strategies most widely used by teachers so that they can improve students' learning abilities.